New Product in Turkey Market: Cold Beverages with Hemp Extract - Aydoğdu, Melike; Döğer, Rukiye; Akgür, Serap Annette (The Bulletin of Legal Medicine, 2017)
Objective: Turkey is important tea markets in the world and ice tea is one of the most popular products in the recent years. In this study, we aimed to evaluated ingredients of the substances written on the can of "Cannabis Ice Tea"; which is presented as psychoactive substance cannabis positive. Materials and Methods: The drink was analyzed by immunoassay and chromatographic methods whether it contains prohibited substance under the relevant legal regulations. In the immunoassay studies; cannabis, cocaine, amphetamines, synthetic cannabinoids, opiates and benzodiazepine groups were analyzed. Cannabis, amphetamines and derivatives, analgesics/nonsteroidal anti-inflammatory drugs (NSAID), antidepressants, antihypertensives, hypnotics/sedatives, neuroleptics, opiates/opioids and caffeine were analyzed by Gas Chromatography-Mass Spectrometry. Results: “Cannabis Ice Tea” was analyzed by immunoassay and parameter results were determined to be negative according to cut off values. The obtained analysis results by chromatographic method; cannabis, amphetamines and derivatives, analgesics/NSAIDs, antidepressants, antihypertensives, hypnotics/sedatives, neuroleptics, opiates/opioids were negative, while caffeine was positive (62 µg/mL). Discussion and Conclusion: Cannabis Ice Tea, which has a big market in the world and is canceled in our country, sales policy for product named as followed by exaggerated taste and sense descriptions. According to the analytical results; caffeine-containing beverage was not containing any cannabis or another prohibited psychoactive substance, can create a potential incentive effect that suggests the use of cannabis in the subconscious mind with a hemp similar logo on ice. In general hemp plant, known to contain psychoactive substances, is required to increased awareness of the use of visuals in sales and necessary legal arrangements, studies and inspections.